The Influence of Financial on Firm Value : Evidence from Indonesia’s 10 Largest Banks (2020–2024) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine the effect of financial ratios on firm value. The ratios used in this study are Non-Performing Loan (NPL), Net Interest Margin (NIM) and Return On Assets (ROA) and Tobin's Q value. This research focuses on the ten largest conventional commercial banks in Indonesia listed on the Indonesia Stock Exchange during the period 2020-2024. Using a descriptive quantitative approach, the population in this study consisted of conventional banks with the highest total assets. The sampling technique used is non-probability sampling with the saturated sampling method, where all members of the population are included as research samples, resulting in 10 banks and 50 observation data points. Panel data regression, t-test, and coefficient of determination analysis were used for data analysis. Data processing was done using EViews 12 software. The results showed that NPL, NIM, and ROA have no significant effect on firm value. These findings suggest that, for Indonesia’s largest conventional banks during 2020–2024, firm value was shaped more by factors beyond credit quality, interest‑spread efficiency, and accounting profitability.
Keywords: Non-Performing Loan; Net Interest Margin; Return On Assets; Firm Value